An overview of periodontal regenerative procedures for the general dental practitioner - M. Siaili; D. Chatzopoulou; D.G. Gillam (Elsevier, 2018)
The complete regeneration of the periodontal tissues following periodontal disease remains an unmet challenge, and has presented clinicians with a remarkably difficult clinical challenge to solve given the extensive research in this area and our current understanding of the biology of the periodontal tissues. In particular as clinicians we look for treatments that will improve the predictability of the procedure, improve the magnitude of the effect of treatment, and perhaps most importantly in the long term would extend the indications for treatment beyond the need for single enclosed bony defects to allow for suprabony regeneration, preferably with beneficial effects on the gingival soft tissues. A rapid development in both innovative methods and products for the correction of periodontal deficiencies have been reported during the last three decades. For example, guided tissue regeneration with or without the use of bone supplements has been a well-proven treatment modality for the reconstruction of bony defects prior to the tissue engineering era. Active biomaterials have been subsequently introduced to the periodontal community with supporting dental literature suggesting that certain factors should be taken into consideration when undertaking periodontal regenerative procedures. These factors as well as a number of other translational research issues will need to be addressed, and ultimately it is vital that we do not extrapolate results from pre-clinical and animal studies without conducting extensive randomized clinical trials to substantiate outcomes from these procedures. Whatever the outcomes, the pursuit of regeneration of the periodontal tissues remains a goal worth pursuing for our patients. The aim of the review, therefore is to update clinicians on the recent advances in both materials and techniques in periodontal regenerative procedures and to highlight the importance of both patient factors and the technical aspects of regenerative procedures. Keywords: Periodontal regeneration, Osseous defects, Guided tissue regeneration, Biomaterials, Enamel matrix derivatives, Case selection